Antimalarial Efficacy of a Quantified Extract of Nauclea pobeguinii Stem Bark in Human Adult Volunteers with Diagnosed Uncomplicated falciparum Malaria. Part 2: A Clinical Phase IIB Trial - Mesia, Kahunu; Tona, Lutete; Mampunza, Ma Miezi; Ntamabyaliro, Nsengi; Muanda, Tsobo; Muyembe, Tamfum; Musuamba, Tshinanu; Mets, Tony; Cimanga, Kanyanga; Totté, Jozef; Pieters, Luc; Vlietinck, Arnold J. (Planta Medica, 2012)
According to the promising results of the Phase I and Phase IIA clinical trials with the herbal medicinal product PR 259 CT1 consisting of an 80 % ethanolic extract of the stem bark of Nauclea pobeguinii containing 5.6 % strictosamide, a Phase IIB study was conducted as a single blind prospective trial in 65 patients with proven Plasmodium falciparum malaria to evaluate the effectiveness and safety of this herbal drug. The study was carried out simultaneously using an artesunate-amodiaquine combination (Coarsucam®) as a positive control. This combination is the standard first-line treatment for uncomplicated malaria recommended by the National Programme of Malaria Control in the Democratic Republic of Congo (DR Congo). With regard to PR 259 CT1, patients were treated with a drug regimen of two 500-mg capsules three times daily for three days in the inpatient clinic, followed by out-patient treatment of one 500-mg capsule three times daily during the next four days; the positive control group received two tablets containing 100 mg artesunate and 270 mg amodiaquine (fixed-dose) once daily during three consecutive days. Antimalarial responses were evaluated according to the WHO 2003 guideline for a 14-day test. The results from the physical and laboratory examinations did not show any significant changes in values of vital signs, ECG, biochemical, and haematological parameters. The study showed a significant decreased parasitaemia in patients treated with PR 29 CT1 and artesunate-amodiaquine with adequate clinical parasitological responses (APCR) at day 14 of 87.9 and 96.9 %, respectively. The former product was better tolerated than the latter since more side effects were observed for the artesunate-amodiaquine combination. These results indicated that PR 259 CT1 can be considered as a promising candidate for the development of a herbal medicine for the treatment of uncomplicated falciparum malaria.
Keywords: Nauclea pobeguinii; Rubiaceae; strictosamide; malaria; Plasmodium falciparum; traditional medicine